Enhancing Students' ICT Literacy Through a Web-Based Project Learning Model - Rahayu Rahayu; Qolbi Khairi (AL-ISHLAH: Jurnal Pendidikan, 2025)
The integration of content components and ICT technology in education is crucial for enhancing student competencies. This study examines the effectiveness of a web-based learning model using project-based learning (PjBL) to improve ICT literacy skills. A quasi-experimental design with a non-equivalent control group was employed. The experimental group was taught using the web-based project learning model, while the control group received traditional instruction. The study involved 60 tenth-grade students from MAN 2 Kota Bengkulu, selected through cluster sampling. Data were collected using a questionnaire, with instrument validity evaluated using the Aiken index and reliability assessed through the Cronbach’s alpha coefficient. Descriptive quantitative analysis was used to interpret the results. The findings indicate a significant difference in ICT literacy skills between the experimental and control groups, as evidenced by a p-value 0.05. This suggests that the web-based project learning model effectively enhances students' ICT competencies. The results highlight the positive impact of integrating web-based project learning on student engagement and ICT skill development. This underscores the necessity of modern teaching approaches in adapting to digital learning environments. The study concludes that web-based project-based learning significantly improves ICT literacy skills. It recommends teacher training programs and curriculum development policies to enhance educators' competencies in technology-enhanced learning. Future research should explore its application across various subjects and educational levels.